Pengaruh Model POGIL (Process Oriented Guided Inquiry Learning) Terhadap Keterampilan Berpikir Kreatif dan Pemahaman Konsep Siswa Pada Materi Redoks - Aprilian, Malisa; Muhali, Muhali; Dewi, Citra Ayu (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This study aims to determine the effect of POGIL to creative thinking skill and conceptual understanding of students at senior high school. This research form of quasi experimental was carried out by postest-only control group design. Research conducted in SMAN1 Montong Gading using sample which determined by saturated sampling technique, 24 number of XA class students as experiment class, and 24 number of XB class students as control class. Creative thinking skills data was collected by observation sheets and conceptual understanding data by reasoning multiple choices test. The results showed that the average creative thinking skill of experimental class at the 1st, 2nd , and 3rdmeeting was 64.388, 72.656, and 79.752.The mean of creative thinking skill of the control class at the 1st, 2nd , and 3rdmeeting was 59.765, 67.447, and 73.476.The hypothesis test result of creative thinking skill data using independent sample t-test it is known that significance value of t-count was 0.040 < 0.05, and conceptual understaning data by paired sample t-test it is known that significance value of t-count was 0.000 < 0.05. So that, there is influence of POGIL model to student creative thinking skill and conceptual understanding.